2020
DOI: 10.1186/s13578-020-00446-8
|View full text |Cite
|
Sign up to set email alerts
|

The functions and mechanisms of prefoldin complex and prefoldin-subunits

Abstract: The correct folding is a key process for a protein to acquire its functional structure and conformation. Prefoldin is a well-known chaperone protein that regulates the correct folding of proteins. Prefoldin plays a crucial role in the pathogenesis of common neurodegenerative diseases (Alzheimer's disease, Parkinson's disease, and Huntington's disease). The important role of prefoldin in emerging fields (such as nanoparticles, biomaterials) and tumors has attracted widespread attention. Also, each of the prefol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 132 publications
0
55
0
Order By: Relevance
“…PFDs are required for normal development of animals and their malfunction, due to mutation or misexpression, is normally associated to cancer or disease (Liang et al, 2020) or causes embryo lethality (Lundin et al, 2008;Delgehyr et al, 2012). Arabidopsis pfd mutants, including the 6x pfd, are viable and do not show apparent developmental defects beyond reduced size, indicating that PFDs' activity is mostly dispensable for normal development in this species (this work; Esteve-Bruna et al, 2020;Rodriguez-Milla and Salinas, 2009;Perea-Resa et al, 2017;Gu et al, 2008).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…PFDs are required for normal development of animals and their malfunction, due to mutation or misexpression, is normally associated to cancer or disease (Liang et al, 2020) or causes embryo lethality (Lundin et al, 2008;Delgehyr et al, 2012). Arabidopsis pfd mutants, including the 6x pfd, are viable and do not show apparent developmental defects beyond reduced size, indicating that PFDs' activity is mostly dispensable for normal development in this species (this work; Esteve-Bruna et al, 2020;Rodriguez-Milla and Salinas, 2009;Perea-Resa et al, 2017;Gu et al, 2008).…”
Section: Discussionmentioning
confidence: 78%
“…The implication of PFDs in other cellular processes is well documented (Liang et al, 2020), however, the lack of systematic genetic analyses makes it difficult to discern whether a particular role is exerted by the canonical PFDc or by individual subunits. For example, PFDN5/MM-1 acts as bridge protein that recruits a corepressor complex to the c-Myc transcription factor (Satou et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prefoldin complex (PFDc) is a heterohexamer present in archaea and eukaryotes, formed by six different subunits named PFD1 to 6 (Liang et al, 2020). It was identified as cochaperone of the cytosolic chaperonin CCT, assisting in the folding of actin and tubulins in yeast and in humans (Vainberg et al, 1998;Geissler et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Arabidopsis mutants deficient in individual PFD genes have defects associated to impaired tubulin folding, such as hypersensitivity to the microtubule-depolymerizing drug oryzalin or disorganized cortical microtubules (Perea-Resa et al, 2017;Rodriguez-Milla and Salinas, 2009;Gu et al, 2008). The activity of PFDs in the cytoplasm is not limited to the folding of tubulins and actin, studies in mammals revealed that they exert a prominent role in preventing the formation of protein aggregates, which otherwise compromise cell viability and cause disease (Liang et al, 2020). For instance, the Huntingtin protein is overaccumulated in the cytosol of cells knocked down for either PFD2 or PFD5, similar to the overaccumulation of the mutant huntingtin protein that causes the Huntington's disease (Tashiro et al, 2013).…”
Section: Introductionmentioning
confidence: 99%